2013
DOI: 10.1016/j.radonc.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Cost of prostate image-guided radiation therapy: Results of a randomized trial

Abstract: The incremental costs due to different prostate IGRT strategies are relatively moderate, suggesting that daily IGRT combined with intensity-modulated RT (IMRT) could be administered in cases of high-dose radiation delivery to the prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 20 publications
1
26
0
1
Order By: Relevance
“…Radiotherapy techniques having evolved dramatically over the last decade, it is not surprising to observe lower patient numbers for all personnel categories in actual radiotherapy practice, as it reflects the increased time demands of the more complex treatment approaches (e.g., IGRT, adaptive radiotherapy) currently used [3][4][5]. In line with this, recommendations about numerical workloads have slightly reduced since the publication of QUARTS [8,15].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Radiotherapy techniques having evolved dramatically over the last decade, it is not surprising to observe lower patient numbers for all personnel categories in actual radiotherapy practice, as it reflects the increased time demands of the more complex treatment approaches (e.g., IGRT, adaptive radiotherapy) currently used [3][4][5]. In line with this, recommendations about numerical workloads have slightly reduced since the publication of QUARTS [8,15].…”
Section: Discussionmentioning
confidence: 97%
“…These factors must all be considered when forecasting radiotherapy personnel requirements. The rapid change in technology and the introduction of new techniques with increased time and resource demands add to the complexity of the task [3][4][5].…”
mentioning
confidence: 99%
“…This may be more important for larger patients who are more likely to roll, with longer time on the treatment couch. Time studies comparing CBCT and EPI acquisition times are scarce for breast RT, however, Perrier et al reported the times for image acquisition comparing CBCT and EPI in prostate cancer, and found that the mean times were 4.6 min (SD: 4.5 min) for CBCT and 3.6 min (SD: 1.6 min) for EPI 37. There are also treatment planning steps that can be taken to address minor daily variations and further reduce the necessity for CBCT use in tangential breast RT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, image-guidance using cone beam computed tomography (CBCT) and implanted fiducial markers further increased the precision of radiation therapy. Image-guided radiation therapy is applied most commonly in genitourinary malignancies, and incremental costs related to online image-guided treatment strategies are acceptable (1,2). Planning studies have demonstrated that IMRT treatment can reduce the dose to OAR compared to 3D-CRT, without a reduction of planning target volume (PTV) coverage (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%